Toward an equilibrium structure in lamellar diblock copolymer thin films using solvent vapor annealing – An in-situ time-resolved GISAXS study. (August 2016) - Sepe, Alessandro; Zhang, Jianqi; Perlich, Jan; Smilgies, Detlef-M.; Posselt, Dorthe; Papadakis, Christine M.
Graphical abstract: Highlights: Structural changes during solvent vapor treatment of thin diblock copolymer films were investigated. Time-resolved grazing-incidence small-angle X-ray scattering revealed significant restructuring. Nearly defect-free lamellar structures having the parallel orientation were generated. Only during the first swelling process, the initial film thickness plays a role. The lamellar thickness in thin film geometry is different from the one in the bulk. Abstract: Solvent vapor annealing (SVA) is frequently used to improve the ordering in diblock copolymer thin films. An important question is which SVA protocol should be chosen to ensure thermodynamic equilibrium. Here, we investigate two thin films from a low molar-mass, lamellae-forming polystyrene- block -polybutadiene (PS- b -PB) diblock copolymer (28.0 kg/mol). The films are prepared by spin-coating Si wafers from toluene solutions and have film thicknesses of 215 nm and 332 nm. The as-prepared films have mainly the parallel lamellar orientation with a lamellar thickness Dlam, par significantly lower than in the bulk. SVA cycles were carried out with cyclohexane, and the structural changes were followed in-situ using time-resolved grazing-incidence small-angle X-ray scattering (GISAXS). Before and after SVA, Dlam, par is significantly lower than in the bulk, i.e. the equilibrium value of Dlam, par in thin film geometry is different from the bulk value. Whereas the behavior of Dlam, par is different for the two films in the early stages of the first swelling, it is very similar in the late stages of swelling and during drying. During the first drying, the lamellae deswell, initially slowly and later, when PS becomes glassy again, affinely. During the second SVA cycle on the thin film, the scaling behavior of the lamellar thickness is identical to the one during the first drying and to the drying behavior of the thicker film. We conclude that one cycle of solvent vapor treatment with a degree of swelling of ca. 1.5 is sufficient to bring the PS- b -PB thin films studied into equilibrium and to create a nearly defect-free lamellar structure.